2015
DOI: 10.1007/s11430-015-5226-z
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and possible origin of the hydrocarbons from Wells Zhongshen1 and Zhongshen1C, Tazhong Uplift

Abstract: In 2013, a great breakthrough of deep petroleum exploration was achieved in the Cambrian pre-salt intervals of Wells Zhongshen1 (ZS1) and Zhongshen1C (ZS1C), Tazhong Uplift. However, the hydrocarbon discovery in the Cambrian pre-salt intervals has triggered extensive controversy regarding the source of marine oils in the Tarim Basin. The geochemistry and origin of the Cambrian pre-salt hydrocarbons in Wells ZS1 and ZS1C were investigated using GC, GC-MS and stable carbon isotope technique. These hydrocarbons c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…5, Table 1), indicating that they derived from a different oil family. Previous reports showed that oils in these wells derived from Cambrian-Lower Ordovician source rocks (e.g., Li et al 2010aLi et al , b, 2012Li et al , 2015Song et al 2016). …”
Section: Microthermometry Of Fluid Inclusionsmentioning
confidence: 96%
See 1 more Smart Citation
“…5, Table 1), indicating that they derived from a different oil family. Previous reports showed that oils in these wells derived from Cambrian-Lower Ordovician source rocks (e.g., Li et al 2010aLi et al , b, 2012Li et al , 2015Song et al 2016). …”
Section: Microthermometry Of Fluid Inclusionsmentioning
confidence: 96%
“…Two typical oil samples collected from Wells TD2 and T904 were also analyzed for comparison. Oils in these two wells are considered to be sourced from Cambrian-Lower Ordovician source rocks (Ma et al 2005;Zhang and Huang 2005;Li et al 2010aLi et al , b, 2012Li et al , 2015Song et al 2016). …”
Section: Geological Settings and Samplesmentioning
confidence: 99%
“…First, vitrinite reflectance cannot be detected to assess maturity, for vitrinite derived from higher plants is absent in marine sediments. Second, conventional molecular organic geochemical maturity parameters, such as biomarker parameters (Song et al, 2016;Song et al, 2017;Xu et al, 2021;Xu et al, 2022, etc), may be invalid at the high-to overmature stage.…”
Section: Maturity Evaluation Of Marine Source Rocksmentioning
confidence: 99%
“…Many factors control the formation of high-quality source rocks, including productivity, the effect of the depositional environment on the preservation of organic matter, and hydrothermal activity (Song et al, 2016;Song et al, 2019;Meng et al, 2022). We studied the sedimentary paleoenvironment and the hydrothermal activity associated with the Dalong Formation high-quality source rocks.…”
Section: Controlling Factors On High-quality Source Rocksmentioning
confidence: 99%